RESPONSIBILITY TO PROTECT OF ROHINGYA REFUGEES: INDONESIAN PERSPECTIVE - Deni Meutia; Harits Dwi Wiratma (Jisiera: The Journal of Islamic Studies and International Relations, 2018)
The research aims to describe the implementation of responsibility to protect concept from military intervention to nonmilitary intervention in Rohingya refugee case. Ethnic conflict in Rakhine, Myanmar has caused many Rohingya people became a refugee in neighboring countries and lead a regional problem. Approximately 700 Rohingya peoples have become a refugee in Aceh, Indonesia as a victim of the ethnic conflict in Rakhine, Myanmar. As a part of international community and maintain regional stability, Indonesia has taken role to protect them. Using the responsibility to protect concept as a nonmilitary approach, this research seeks to point out Indonesia’s perspective in protecting the victim of the Rohingya ethnic conflict. Humanity became the main basis of Indonesia action. The result showed what has been done by Indonesia is in accordance with the principle of responsibility to protect.